Pengaruh Rasio Profitabilitas, Likuiditas, Solvabilitas, Struktur Kepemilikan Institusional, dan Struktur Kepemilikan Manajerial, Terhadap Kesulitan Keuangan (Dengan Model Altman Z-Score) (Studi Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek - Rini Susanti; Wiwin Wahyuni (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This study aims to see how the development of the financial performance of manufacturing companies listed on the Indonesia Stock Exchange for the last 3 years from 2017 to 2019 using the financial ratio analysis method. The financial ratios used are Profitability, Liquidity, Solvency, Institutional Ownership Structure, and Managerial Ownership Structure. The results showed that in general the financial ratios of manufacturing companies listed on the Indonesia Stock Exchange fluctuated, but among them there were several companies that had good financial ratios and poor financial ratios.